2021
DOI: 10.3390/jcm10081693
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Lipoprotein Dysregulation in Sepsis: Clinical and Mechanistic Insights into Chronic Critical Illness

Abstract: In addition to their well-characterized roles in metabolism, lipids and lipoproteins have pleiotropic effects on the innate immune system. These undergo clinically relevant alterations during sepsis and acute inflammatory responses. High-density lipoprotein (HDL) plays an important role in regulating the immune response by clearing bacterial toxins, supporting corticosteroid release, decreasing platelet aggregation, inhibiting endothelial cell apoptosis, reducing the monocyte inflammatory response, and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 205 publications
(118 reference statements)
1
49
0
1
Order By: Relevance
“…Both CETP and PLTP are part of the lipid-transfer and LPS-binding proteins ( Hubacek et al, 1997 ; Kirschning et al, 1997 ; Levels et al, 2005 ). CETP can transfer CE via hydrophobic tunnels from HDL to LDL and VLDL, while PLTP transfers PL to HDL ( Zhang et al, 2012 ; Barker et al, 2021 ). PLTP and CETP may protect against endotoxins and were considered to enhance LPS elimination ( Kirschning et al, 1997 ; Cazita et al, 2008 ; Gautier et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both CETP and PLTP are part of the lipid-transfer and LPS-binding proteins ( Hubacek et al, 1997 ; Kirschning et al, 1997 ; Levels et al, 2005 ). CETP can transfer CE via hydrophobic tunnels from HDL to LDL and VLDL, while PLTP transfers PL to HDL ( Zhang et al, 2012 ; Barker et al, 2021 ). PLTP and CETP may protect against endotoxins and were considered to enhance LPS elimination ( Kirschning et al, 1997 ; Cazita et al, 2008 ; Gautier et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another enzyme involved in lipoprotein metabolism is endothelial lipase, which is a driving factor for hydrolyzation of phospholipids (PL) of HDL particles. Furthermore, CETP transfers CE from HDL to low-density (LDL) and very low-density lipoproteins (VLDL) in exchange for triglycerides (TG), while the phospholipid transfer protein (PLTP) transfers PL from triglyceride-rich lipoproteins to HDL ( Deckert et al, 2017 ; Trinder et al, 2019 ; Tanaka et al, 2020 ; Barker et al, 2021 ). PLTP may also transfer LPS from bacteria to HDL ( Vesy et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it has been suggested that HDL particles could have a therapeutic role in the treatment of sepsis [ 54 ]. Three metabolomic studies on adults reported that total cholesterol; non-HDL cholesterol; apolipoprotein (Apo)-A1, a major component of HDL [ 55 ] through which HDL binds to lps [ 56 ]; Apo-B100, a component of LDL, VLDL and intermediate-density lipoprotein (IDL) which is involved in the development of atherosclerosis [ 57 ]; HDL Apo-A1; HDL cholesterol; LDL cholesterol; and HDL-free cholesterol were reduced in sepsis patients compared to intensive care [ 39 ] and healthy controls [ 43 , 44 ], whilst VLDL-free cholesterol, triglycerides (TG) and VLDL triglyceride subfractions 4 and 5, VLDL Apo-B100 and Apo-B100 to Apo-A1 ratio were elevated [ 39 ]. These results suggest decreased neutralisation and clearance of bacterial toxins via the liver [ 58 ], increased TG production, reduced lipoprotein lipase activity and enhanced production or reduced clearance of VLDL [ 55 , 59 ].…”
Section: Metabolomics To Identify Diagnostically Useful Clinical Phen...mentioning
confidence: 99%
“…As previously described, HDL is the lipoprotein which possesses the highest affinity for both the Gram-positive and Gram-negative bacterial toxins LTA [ 111 ] and lps [ 54 , 112 ] and binds them via apolipoprotein-(Apo)-A1, a major component of HDL [ 55 ]. HDLs have several different roles during the acute stress response, such as promoting clearance of bacterial toxins, reducing platelet aggregation, inhibiting endothelial cell activation and apoptosis [ 113 ] and supporting the corticosteroid stress response [ 56 ]. Reduced levels of HDL, LDL and Apo-A1 were consistently reported in non-survivors in comparison to survivors of sepsis [ 89 , 97 , 98 ], which could lead to worse outcomes through many of the mechanisms described above, but specifically, the inability to clear lps may lead to acute lung and kidney injury [ 114 ].…”
Section: Metabolomics To Identify Prognostically Useful Clinical Phen...mentioning
confidence: 99%
“…HDL exhibits pleiotropic effects during the acute inflammatory response, including clearing bacterial toxins, supporting corticosteroid release, decreasing platelet aggregation, inhibiting endothelial cell apoptosis, reducing the monocyte inflammatory response and inhibiting expression of endothelial cell adhesion molecules [4]. In severe sepsis, serum cholesterol levels drop nearly 50% [5].…”
Section: Introductionmentioning
confidence: 99%